Intestinal Microbiota in Neonates and Preterm Infants: A Review - France de La Cochetiere, Marie; Rouge, Carole; Darmaun, Dominique; Christophe Roze, Jean; Potel, Gilles; Gras Leguen, Christele (Current Pediatric Reviews, 2007)
The fetal gastrointestinal tract is sterile until birth when microbes colonize the gastrointestinal tract, and a dense, complex microbiota develops. This enormous cell mass performs a variety of activities that affect both the intestinal and systemic physiology. The microbiota provides nutritional, metabolic, immunological, and protective functions. The neonatal gastrointestinal tract is an organ at risk. Increasing awareness that the human flora is a major factor in both health and disease has led to different strategies to manipulate the flora. Manipulation with prebiotics and probiotics has shown promising results although a better understanding of the gut bacterial colonization process is required before attempts to change the flora should be made. In this review, we summarize the data regarding developmental microbial ecology in the neonatal gastrointestinal tract, and the modulation of such microbiota. The discussion focuses on the control and manipulation of bacterial colonization in the neonatal gut for the prevention and treatment of bacterial intestinal disease in both in human infants and on animal models. Since the best available methodologies should be utilized in studies of nutritional sciences, a recapitulation of the latest techniques for the study of the gastrointestinal flora is presented. Future progress is likely to arise from the use of genomic techniques to track of dietinduced changes in microbiota.
Keywords: microbiota